Three-Component Chlorophosphinoylation of Alkenes via Anodically Coupled Electrolysis - Lu, Lingxiang; Fu, Niankai; Lin, Song (Synlett, 2019)
We report the development of an electrocatalytic protocol for the chlorophosphinoylation of simple alkenes. Driven by electricity and mediated by a Mn catalyst, the heterodifunctionalization reaction takes place with high efficiency and regioselectivity. Cyclic voltammetry data are consistent with a mechanistic scenario based on anodically coupled electrolysis in which the generation of two distinct radical intermediates occur simultaneously on the anode and are both mediated by the Mn catalyst.
Keywords: electrochemistry; electrocatalysis; anodically coupled electrolysis; alkene difunctionalization; radical addition; chlorination; phosphine oxide